Komunikasi Politik Presiden Joko Widodo dalam Lawatannya ke Ukraina dan Rusia - Tri Setiawan (CV. Ulil Albab Corp, 2023)
This research is motivated by the political communication of President Joko Widodo in his visit to Ukraine and Russia. Political communication is an inseparable part of the political dynamics in which communication works. This research uses a literature study approach related to theoretical studies and other references related to political and social value issues. The results of the study explain that Joko Widodo's political communication on his visit to Ukraine and Russia to convey a message of peace with the President of Ukraine with the sentence Manifestation of Indonesia's concern for the situation in Ukraine, namely Indonesia wants to establish cooperation with Ukraine both politically and economically. In fact, Ukraine is one of the largest wheat producers in the world today. But President Zelenskyy wants bilateral cooperation between the two countries both in the political and economic fields. President Jokowi also conveyed the message of peace to the Russian leader with a subtle phrase by positioning himself as a mediator I became a bridge of communication between the two leaders, this phrase is a safe and subtle method so as not to corner one of the parties, either Russia or Ukraine. President Putin pointed out that the peace mission brought by Jokowi was not responded to by Putin.